PENGARUH SEKTOR KETENAGALISTRIKAN TERHADAP PEREKONOMIAN NASIONAL: ANALISIS INPUT-OUTPUT - Kristiana Kristiana; Socia Prihawantoro; Joko Santosa (Badan Pengkajian dan Penerapan Teknologi, 2020)
Economists argue that the growth of GDP per capita in a country is greatly influenced by the growth inelectricity consumption in that country. The meaning of this statement is that if you want to increaseGDP per capita, the important thing that needs to be done is to increase the electricity supply capacity.Empirical data shows that every 1 kWh (kilowatt-hour) of electricity consumption contributes about 4 - 5 to GDP. Another study also states that every 1000 MW of installed capacity will contribute to a GDPof around 16 billion or equivalent to Rp. 200 trillion. Therefore, if Indonesia wants to become a countrywith the fifth-largest economy in the world with a GDP of 5.420 trillion in 2030, then one way that canbe taken is to increase the capacity of electricity resources to a minimum of 120,000 MW in 2025(RUEN, 2017). This background underlies the analysis of the relationship between the growth of theelectricity sector and the growth of the national economy. The analysis method that will be used is theanalysis of the economic impact with the Input-Output (I-O) method. Furthermore, the I-O table usedfor analysis is the 2014 creative economy I-O table. Based on the results of the study analysis, it isstated that the sub-sector that has high leverage is the sub-sector for electricity supply. However, tohave an impact on the national economy caused by the growth of the electricity sector, it is alsonecessary to develop the five sub-sectors holistically. The results of this study are expected to provideinput for stakeholders in formulating policies for the development of the electricity sector as an effort toachieve the target of advanced Indonesia in 2030.